2021
DOI: 10.3892/ol.2021.12991
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of bevacizumab in combination with fluoropyrimidine drugs on human oral squamous cell carcinoma

Abstract: Vascular endothelial growth factor (VEGF) serves an important role in new blood vessel formation or angiogenesis, which is a critical event in tumor growth and metastasis. Bevacizumab is a humanized monoclonal antibody against VEGF-A, whereas S-1 is a fluoropyrimidine antineoplastic agent that induces apoptosis in various types of cancer cells. The present study evaluated the antitumor effects of bevacizumab in combination with 5-fluorouracil (5-FU) or S-1 against oral squamous cell carcinoma (OSCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
3
6
0
1
Order By: Relevance
“…On the other hand, It was previously reported, that positive expression of CD44 actively interacts with surrounding stromal cells in the tumor microenvironment. The tumor cells incorporate pre-existing vessels and utilize the perivascular niche for their survival (Krishnamurthy et al, 2010). in addition, Some studies observed that positive cells of CD44 are located in the perivascular niche in the models as well as in human tumor tissues.…”
Section: Head and Neck Squamous Cell Carcinomas ]Hnsccs[ Is Considere...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, It was previously reported, that positive expression of CD44 actively interacts with surrounding stromal cells in the tumor microenvironment. The tumor cells incorporate pre-existing vessels and utilize the perivascular niche for their survival (Krishnamurthy et al, 2010). in addition, Some studies observed that positive cells of CD44 are located in the perivascular niche in the models as well as in human tumor tissues.…”
Section: Head and Neck Squamous Cell Carcinomas ]Hnsccs[ Is Considere...mentioning
confidence: 99%
“…VEGF is considered as a homodimeric glycoprotein with a molecular weight of about 45 kDa, which is the main key of angiogenesis in cancer, in which it is regulator by oncogene expression (Carmeliet, 2005). VEGF-Atargeting monoclonal antibody therapies have provided successful results in diverse types of cancer like colorectal cancer and head and neck cancer (Itashiki et al, 2021). Bevacizumab is a molecularly targeted medication with different Characteristics compared with conventional chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Хотя показатели выживаемости при плоскоклеточном раке полости рта улучшились за последние два десятилетия, прогноз все еще остается неблагоприятным по сравнению с развитием терапии и успехом, достигнутым для других видов злокачественных опухолей. Прогностические факторы многочисленны, а их взаимодействия сложны и до сих пор неясны [12][13][14].…”
Section: актуальностьunclassified
“…In contrast, other studies found no significant differences in VEGF-A expression in human oral SCC compared to epithelial dysplasia or normal gingiva [ 81 , 82 ]. Furthermore, treatment with the VEGF-A antagonist bevacizumab, alone or in combination with 5-fluorouracil chemotherapy, failed to inhibit human oral SCC cell proliferation in vitro [ 83 ]. With regard to PLGF, transcripts and protein levels were upregulated in human oral SCC compared to normal tissue.…”
Section: Introductionmentioning
confidence: 99%